2010
DOI: 10.3989/scimar.2010.74n3605
|View full text |Cite
|
Sign up to set email alerts
|

Relationships between otolith size and fish size in some mesopelagic and bathypelagic species from the Mediterranean Sea (Strait of Messina, Italy)

Abstract: SUMMARY: The length-weight relationships and the regressions between otolith size (length and width) and fish length of some mesopelagic and bathypelagic fishes living in the central Mediterranean Sea were provided. Images and morphological description of otoliths (sagittae) from 16 species belonging to the families of Gonostomatidae (1), Microstomatidae (2), Myctophidae (8), Phosichthyidae (2), Sternoptychidae (2) and Stomiidae (1) were given. The length-weight relationship showed an isometric growth in 13 sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
137
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 103 publications
(158 citation statements)
references
References 36 publications
(38 reference statements)
6
137
1
Order By: Relevance
“…The relationship between otolith length width and fish body proportions is related to the growth rate of the fish (Mugiya and Tanaka, 1992) and these relationship became curvilinear in some larval or juvenile fishes (West and Larkin, 1987), such curvilinearity was observed in the present study, but not in the previous similar studies on fishes from Oman (Al-Mamry et al, 2010;Jawad et al, 2011a;Jawad and Al-Mamry, 2012). Harvey et al (2000), Waessle et al (2003) and Battaglia et al (2010) have suggested that there is a possibility of getting error in the final results of the relationship between otolith dimensions and fish size due to changes in this relationship during the life history of the fish and as the fish length changes (Frost and Lowry, 1981;Hare and Cowen, 1995).…”
Section: Discussioncontrasting
confidence: 43%
See 3 more Smart Citations
“…The relationship between otolith length width and fish body proportions is related to the growth rate of the fish (Mugiya and Tanaka, 1992) and these relationship became curvilinear in some larval or juvenile fishes (West and Larkin, 1987), such curvilinearity was observed in the present study, but not in the previous similar studies on fishes from Oman (Al-Mamry et al, 2010;Jawad et al, 2011a;Jawad and Al-Mamry, 2012). Harvey et al (2000), Waessle et al (2003) and Battaglia et al (2010) have suggested that there is a possibility of getting error in the final results of the relationship between otolith dimensions and fish size due to changes in this relationship during the life history of the fish and as the fish length changes (Frost and Lowry, 1981;Hare and Cowen, 1995).…”
Section: Discussioncontrasting
confidence: 43%
“…It is a common in the fisheries studies to use otolith width and height as variables for valuing fish size (Battaglia et al, 2010;. The present study puts forward the equations based on otolith length and width dimensions in relation to fish total, standard and head length of the blackspot snapper L. ehrenbergii from the Omani waters for the first time.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…There are many studies that determine the otolith biometry and relationships between fish size (Waessle et al, 2003;Gümüs & Kurt, 2009;Battaglia et al, 2010;Keskin;Sadighzadeh et al, 2014). Sexual differences in relationships between otolith biometry and fish size were identified in this study, which have been reported for many species (Vallisneri et al, 2008;Bostanci et al, 2012).…”
Section: Resultsmentioning
confidence: 60%